Characteristics and Accumulation Model of Silurian Tight Sandstone Gas Reservoir: A Case Study in the Shajingzi Belt, Northwest Tarim Basin, China - Zhang, Yuanyin; Zhang, Junfeng; Gao, Yongjin; Liu, Yalei; Miao, Miaoqing; Li, Qingyao; Sun, Zhichao (Frontiers in Earth Science, 2022)
The first industrial gas flow has been recently achieved in the Shajingzi Belt, northwest Tarim Basin, China, although that area is always characterized as a monoclinic structure background, typical tight bituminous sandstones, and poor hydrocarbon accumulation conditions. Based on drilling, oil testing, geophysics, geological, and geochemical data, a comprehensive research including reservoir description, hydrocarbon tracing, and accumulation history analysis in the Shajingzi Belt was carefully conducted to establish a meaningful Silurian hydrocarbon accumulation model and discover potential areas in this study. It is found that 1) the Silurian reservoirs in the Shajingzi Belt mainly bear gas and could be defined as the typical tight sandstone reservoir with ultralow porosity generally less than 10% and low-permeability distributed between 0.1 and 10 mD, respectively; 2) petroleum substantially comes from the Cambrian–Ordovician source rocks, especially in the Awati Sag, possessing the dominant contribution from the shales in Cambrian Yuertusi Formation; 3) synthetically, three major hydrocarbon accumulation periods can be determined in the Shajingzi Belt, namely, the Late Caledonian, the Late Hercynian–Early Indosinian, and the middle Himalayan, respectively; 4) the evolution of Shajingzi Fault system apparently dominated the formation of various Silurian structural–lithologic traps in the monoclinic structure background and efficiently connected the deep source rocks in the Awati Sag, especially during Himalayan period when the current tight sandstone gas reservoirs were formed. This research could find its benefit for exploration in similar basin–range junction areas.